UPAYA GURU DALAM MELATIH KEMANDIRIAN ANAK USIA DINI DI TK ADE IRMA SURYANI SCHOOL - Rahmawati Agustina; Novita Friska; Aminda Tri Handayani; Juli Yanti Harahap (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Independence is one of the important aspects in the social and emotional development of early childhood, which needs to be instilled from an early age so that children have the ability to take care of themselves, be responsible, and be able to make simple decisions. This study aims to describe in depth the efforts of teachers in training the independence of early childhood at Ade Irma Suryani, as well as to identify the supporting and inhibiting factors in its implementation. This study uses a qualitative approach with a descriptive research type. The research subjects consisted of three classroom teachers, one principal, and six early childhood children as supporting informants. Data collection techniques were carried out through observation, in-depth interviews, and documentation. Data analysis was conducted using the Miles and Huberman interactive model, which includes data reduction, data presentation, and conclusion drawing and verification. The results of the study indicate that teachers at Ade Irma Surya School foster children's independence through various strategic efforts, including providing routine habits, giving simple responsibilities, and providing motivation and positive praise for every effort made by the children. Teachers also use play-based learning methods, role modeling, and provide opportunities for children to choose and decide on simple matters related to daily activities. Supporting factors in fostering children's independence include parental support at home, a conducive and child-friendly school environment, high child motivation, and the availability of adequate facilities and infrastructure. Meanwhile, inhibiting factors include overprotective parenting, differences in children's levels of independence, and limited learning time at school.